A New Teleworking Growth Model - Florina Bran; Maria-Daniela Tudorache; Andreea Florentina Nicolescu; Dumitru Alexandru Bodislav; Mihaela Diana Oancea Negescu; Maria Loredana Popescu (Economic Computation and Economic Cybernetics Studies and Research, 2022)
This paper assesses the impact of telework on economic growth in the European Union using Feasible Generalized Least Squares method, applied to a Panel of 27 Member States, in the period 2010-2019. The econometric model also analyses the impact of the rate of employed population not working from home on the economic growth, to facilitate the comparative analysis of telework and traditional work. The results indicate a greater impact of telework on economic growth, than that exerted by the rate of employed population not working from home, the effect being manifested through the channel of labour productivity. However, the paper examines the short-term relationship between these variables and does not exclude the reduction of the impact of telework on economic growth to a lower level than the specific effect of traditional work, on medium or longterm.
Keywords: J08; J21; O47; 330; telework; economic growth; productivity; impact; model; European Union